Reviewing the Anthropological Study of Tharus in Nepal - Kharel, Megh Prasad (Tribhuvan University Journal, 2019)
This paper aims to review the varieties of Tharu anthropological writings in Nepal. It is clear that the basic notion of reviewing any area study is to pave the way for further studies as it reveals the departure and gap from previous study. At this backdrop, the review on anthropological study of Tharu in Nepali socio-cultural context discusses how the writings dealing with the Tharus community seem helpful for opening the way to further studies in this area of ethnicity with multidisciplinary approaches, such as, cultural studies, linguistics, literature, demography, history, folklore, sociology, arts and crafts and ethnography. At the same time, it also enhances to comprehend varied subgroups of Tharus in Nepal, for instances, Dangaura, Rana, Kochila, Chitwaniya and Desaura. Moreover, the present research on Tharus is comparatively more focused on anthropological study rather than other disciplines, such as, folklore, ethno-music and literature, sociology, cultural studies, linguistics, ethno-history and demography. Regarding the Tharu anthropological research, this study is an attempt to portray the huge possibility of further ethnic studies, particularly on many subgroups of Tharus in Nepali territory.